INOVASI PEMBELAJARAN MATEMATIKA DALAM MENINGKATKAN PROFESIONALISME GURU DENGAN MENGGUNAKAN VIDEO CONFERENCE JITSI - Camelia Nailul Agustina Roesindiyanti (LPPM Universitas Advent Indonesia, 2022)
Students' difficulty in understanding mathematics requires the teacher's role to be creative, adaptive, and innovative in carrying out learning using the methods, strategies, and media used. So that teachers need to make learning innovations which in this case is a form of teacher professionalism. The purpose of this study is to analyze learning innovations that can be carried out by using one of the devices, namely the Jitsi video conference in order to improve the professionalism of a teacher, especially during a pandemic like today. The method used is library research by collecting various references in the form of books, relevant national and international journals and using deductive data analysis with data collection techniques involving several processes, namely organizing, editing and analyzing. The results of this study indicate that one of the learning innovations that can be used is the use of jitsi video conference so that mathematics learning is more effective and efficient. With effective and efficient learning, it can be said that the professionalism of teachers is also getting better.